A Qualitative Analysis of Experiences of Suicidal Ideation and Suicide Commitment among Females with Major Depressive Disorder in Pakistan - Qamar, Tania; Chethiyar , Saralah Devi Mariamdaran; Ibrahim, Nabisah binti (South Asian Journal of Social Sciences and Humanities, 2021)
Purpose. Suicide is a global public health problem. Because Asia accounts for 60% of all  suicides worldwide, at least 60 million people are impacted by suicide or commit suicide in  Asia each year. Females are more likely than males to engage in suicidal behaviour, which is  defined as a complete problem of illness and death. The aim of the present research was to  identify experiences of suicidal ideation and suicide commitment among females with major  depressive disorder in Pakistan. Method. A sample of approximately 5 clients with major  depressive disorder were approached from (Captain Mouzam Ali Shaheed Welfare Trust  Hospital, Jhelum) Pakistan. The sample collected through snowball sampling strategy.  Qualitative method of in-depth semi structured interview was conducted in order to get data.  Beck depression inventory and suicide risk screener was used as an assessment measure. Ideographic Phenomenological Data Analysis (IPA) was utilized to examine and recorded the  information in which investigator identified themes. Specific verification method was utilized to measure the credibility of the research results. Results. In outcomes, the main themes  emerged in the current study and figures were drawn in order to explain the different themes. There were seven main themes were emerged in the present research were named as Etiology  of Major Depressive Disorder (MDD), Effects of MDD, Psychosocial Factors, Coping with  MDD, Insight about MDD, Seeking Support and Experience Difficulties During the Treatment  of MDD. Novelty/Originality of The Study. Suicidal thoughts were moderately common  among patients with major depressive illness. Implication. As a result, all clients with major  depressive illness should be screened for suicide thoughts so that treatment can begin as soon  as possible.
Keywords: Suicidal Ideation; Suicide Commitment; Major Depressive Disorder; Married Females; Ideographic Phenomenological Data Analysis (IPA)